Answer:
6.4
Step-by-step explanation:
The whole thing is like a triangle, with the distance between the points as the hypotenuse.
Use the pythagorean theorem, a²+b² = c².
To calculate a, calculate the distance between the x-values of (-5,-1) and (0.3) by subtracting.
0-(-5) = 5
a = 5
To calculate b, calculate the distance between the y-values of (-5,-1) and (0.3) by subtracting.
3-(-1) = 4
b = 4
now plugin a = 5 and b = 4 into the pythagorean theorm to calculate c, or the distance.
5²+4² = c²
25+16 = c²
41 = c²
√41 = √c²
c = 6.4